Synthesis and evaluation of a 68Ga labeled folic acid derivative for targeting folate receptors. (October 2016) - Jain, Akanksha; Mathur, Anupam; Pandey, Usha; Bhatt, Jyotsna; Mukherjee, Archana; Ram, Ramu; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract: Present work evaluates the potential of a newly synthesized 68 Ga-NOTA-folic acid conjugate for PET imaging of tumors over-expressing folate receptors (FRs). NOTA-folic acid conjugate was synthesized and characterized. It was radiolabeled with 68 Ga in ≥ 95% radiolabeling yields. In vitro cell binding studies showed a maximum cell uptake of 1.7±0.4% per million KB cells which was completely blocked on addition of cold folic acid showing specificity towards the FRs. However, further studies in tumor xenografts are warranted in order to assess the potential of 68 Ga-folic acid complex for imaging tumors over-expressing FRs. Highlights: NOTA-Bn-(3-aminopropyl) folic acid conjugate was synthesized and characterized by 1 H-NMR, ESI-MS and HPLC analysis. NOTA-folic acid conjugate radiolabeled with 68 Ga in >95% yields and high serum stability (≥95%) upto 1 h. In vitro studies in KB cells showed specificity of NOTA-Bn-(3-aminopropyl) folic acid. A maximum cell uptake of 1.7±0.4% per million KB cells was observed for 68 Ga-NOTA-folic acid.